Perwujudan Nilai Transparansi, Akuntabilitas dan Konsep Value For Money dalam Pengelolaan Akuntansi Keuangan Sektor Publik - Sayuti Sayuti; Jamaluddin Majid; Sapril Sardi Juardi (Atestasi : Jurnal Ilmiah Akuntansi, 2018)
This study aims apalication the values of transparency, accountabily and value for money in the accounting financial management of Agency Regional Development Planning (BAPPEDA) kabupaten gowa. Beside that, research this iam for knowing aplication the concept of value for money on the perormance of the wokr program that has been impementation. Objects research in reseacrh this is wrong one istitute goverment namely the Regional Development Planning Agency (BAPPEDA), Method data retrieval (field reseacrh), interview directly with informants, studies library dan internet searching, interview do with internal parties. Results reseacrh thisobtained that per manifestation of the value has been applied to the disclosure of information and the value of accountability to the public and the goverment in accordance with the rules, in the procces of financial management accounting by using a system of accrual, the concept of value for money is quets economical, efficient, effective in Agency Regional Development Planning (BAPPEDA) kabupaten Gowa corresponding with rules that have been set by goverment.